The heavy rains and floods on 17 and 18 December 2016 in the Region of Murcia, with particular focus on the Mar Menor Watershed - D. Espín Sánchez; R. García Lorenzo; V. Ruiz Álvarez; C. Conesa García (Ingeniería del Agua)
The heavy rains on December 17-18, 2016 were one of the most significant events that have occurred in southeastern Spain over the last two decades. In the present study the incidence of these rains in the Region of Murcia, and especially in the Mar Menor watershed, is analyzed, with particular focus on the flooded areas. The synoptic situation and the atmospheric dynamics were studied through monitoring of different METEOSAT´s satellite bands, images from weather radars and data from atmospheric soundings. A map showing the accumulated rainfall during the event and another one concerning the pluviometric anomaly of December 2016 in comparison with the average for this month in the period from 1981 to 2010 were produced using precipitation data of 129 weather stations belonging to different organizations. The maximum precipitation reached in 1 and 12 hours for a total of 64 stations was also analyzed, in relation to the thresholds and alarm levels which are established by AEMET. Finally, two hydrometeorological methods, the SCS Dimensionless Unit Hydrograph -SCS DUH- and the Témez’s Unit Hydrograph Method -TUH-, were used in order to estimate the flood-peak discharges in ephemeral streams flowing to the Mar Menor, which led to flooding in the Alcazares area. In accordance with the more consistent results of SCS DUH, the flood-peak discharges caused in this area by the Albujón and Maraña ramblas were estimated to be around 820 and 258 m3/s respectively.